MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA MADRASAH TSANAWIYAH MENGGUNAKAN MEDIA GAMBAR - Suparlan, Suparlan; Mahsar, Lalu (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The aim of this research was to improve the English communication skills of the students of the second grade of Madrasah Tsanawiyah Darul Aminin NW Aikmual Central Lombok by using images media to determine the use of images media to improve speaking skills and determine students' speaking abilities after using images media. This research uses classroom action research (CAR). The results of the research are as follows. First, by applying images media can develop students' speaking skills. Students can communicate communicatively, orderly, well, and correctly, this can be seen after conducting classroom action research. Second, by applying images media to the learning process in order to improve students' speaking skills, it can be seen in the increase in the results of speaking skill scores. The subjects of this research were second grade of the students of Madrasah Tsanawiayah Darul Aminin NW Aikmual Lombok Tengah which consisted of 17 students consisting of boys and girls taken from 31 students in class B. The object of this research was the second grade of Madrasah Tsanawiyah Darul Aminin NW Aikmual Lombok Tengah.